Effectiveness of Guided Inquiry Learning Tools to Improve Understanding Concepts of Students on Momentum and Impulse Materials - Susilawati Susilawati; Aris Doyan; Lalu Muliyadi (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to the effectiveness of guided inquiry learning tools to improve understanding concepts of students on momentum and impulse materials. The learning device was developed using a 4D model consisting of four steps, namely define, design, develop and disseminate. This research was conducted at SMAN 4 Mataram in the tenth grade of MIPA 1 with a total of 20 people. The data was obtained in the form of pre-test and post-test scores. The data were analyzed using the Shapiro Wilk test and paired sample t-test at a significance level of 5%. The results of the Shapiro Wilk test show that the data are normally distributed and meet the requirements to perform a parametric test. The results of the paired sample t-test show that the t-count (24.347) is greater than the t-table (2.093). This means that there is influence of guided inquiry learning tools improves understanding concepts of students. These results indicate that the guided inquiry learning model is effective to improve understanding concepts of students on momentum and impulse materials